2014
DOI: 10.1002/jat.3041
|View full text |Cite
|
Sign up to set email alerts
|

Diisocyanates, occupational asthma and IgE antibody: implications for hazard characterization

Abstract: Sensitization of the respiratory tract by chemicals resulting in rhinitis and asthma is an important occupational health issue. Occupational asthma is associated with significant morbidity and can be fatal. Tests for the identification and characterization of chemicals with the potential to cause sensitization of the respiratory tract are lacking. In spite of sustained interest there are no validated or widely accepted methods available, and this presents toxicologists with a considerable challenge. One import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…GSH is the major free thiol of the lower airway fluid, where it is normally present at relatively high levels compared with peripheral blood [28,29]. Accordingly we found the higher GSH concentration in BALF.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…GSH is the major free thiol of the lower airway fluid, where it is normally present at relatively high levels compared with peripheral blood [28,29]. Accordingly we found the higher GSH concentration in BALF.…”
Section: Discussionsupporting
confidence: 60%
“…Animal experimental studies have suggested for albumin the possible existence of a “shuttle” mechanism through which diisocyanate is transported from the airways to the blood. The formation of antigenic diisocyanate-albumin conjugates mediates the pathogenic responses to occupational exposure, like the production of cytokine, specific IgE, oxidative stress, and innate immune proteins [28,29]. In the serum of exposed workers diisocyanate-albumin specific IgG is frequently found, and IgE isotypes are rarely observed [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the greatest uncertainty is the role of IgE antibody in sensitisation of the respiratory tract to chemicals. Although the majority, if not all, chemical respiratory allergens have been associated with the production in sensitised subjects of IgE antibody, it is the case that in many instances -and in particular with the diisocyanates -patients with chemical respiratory allergy and occupational asthma lack detectable IgE antibody Isola et al, 2008;Kimber et al, 2014a). For reasons that are outside the scope of this paper, it may be the case that the correlation between IgE antibody production and chemical respiratory allergy is underestimated.…”
Section: Mechanisms Through Which Sensitisation Of the Respiratory Trmentioning
confidence: 64%
“…For reasons that are outside the scope of this paper, it may be the case that the correlation between IgE antibody production and chemical respiratory allergy is underestimated. It could even be the case that IgE antibody plays a mandatory and universal role in sensitisation of the respiratory tract to chemicals, but this is unproven Jones et al, 2003;Kimber et al, 2014a). Nevertheless, it must be acknowledged that there may exist IgE antibody-independent mechanisms through which sensitisation of the respiratory tract to chemicals may be acquired.…”
Section: Mechanisms Through Which Sensitisation Of the Respiratory Trmentioning
confidence: 93%